Craniofacial Surgery and Adverse Outcomes: An Inquiry Into Medical Negligence. (July 2015) - Svider, Peter F.; Eloy, Jean Anderson; Folbe, Adam J.; Carron, Michael A.; Zuliani, Giancarlo F.; Shkoukani, Mahdi A.
Objective: This study aimed to evaluate factors contributing to medical negligence relevant to craniofacial surgery. Methods: Retrospective analysis of verdict and settlement reports on the Westlaw legal database for outcome, awards, physician defendants, and other specific factors raised in malpractice litigation. Results: Of 42 verdicts and settlement reports included, 52.4% were resolved with either an out-of-court settlement or plaintiff verdict, with aggregate payments totaling $50.1M (in 2013 dollars). Median settlements and jury-awarded damages were $988 000 and $555 000, respectively. Payments in pediatric cases ($1.2M) were significantly higher. Plastic surgeons, oral surgeons, and otolaryngologists were the most commonly named defendants. The most common alleged factors included intraoperative negligence (69.0%), permanent deficits (54.8%), requiring additional surgery (52.4%), missed/delayed diagnosis of a complication (42.9%), disfigurement/scarring (28.6%), postoperative negligence (28.6%), and inadequate informed consent (20.6% of surgical cases). Failure to diagnose a fracture (19.0%) and cleft-reparative procedures (14.3%) were the most frequently litigated entities. Conclusion: Medical negligence related to craniofacial surgery involves plaintiffs in a wide age range as well as physician defendants in numerous specialties, and proceedings resolved with settlement and plaintiff verdict involve substantial payments. Cases with death, allegedly permanent injuries, and pediatric plaintiffs had significantly higher payments.